Direct microbial conversion of biomass to advanced biofuels - Himmel, Michael E. (Amsterdam : Elsevier, 2015)
'Direct Microbial Conversion of Biomass to Advanced Biofuels' is a stylized text that is rich in both the basic and applied sciences. It provides a higher level summary of the most important aspects of the topic, addressing critical problems solved by deep science. Expert users will find new, critical methods that can be applied to their work, detailed experimental plans, important outcomes given for illustrative problems, and conclusions drawn for specific studies that address broad based issues. A broad range of readers will find this to be a comprehensive, informational text on the subject matter, including experimentalists and even CEOs deciding on new business directions.
Substrate Recalcitrance and Cellulase MixturesLytic Polysaccharide Monooxygenases; Conclusion; References; Chapter 7 -- New Insights into Microbial Strategies for Biomass Conversion; Introduction; Distinct Enzyme Synergy Paradigms in Cellulolytic Microorganisms; New Cellulose Digestion Strategies Promoting Interspecies Synergism; Future Perspective; References; Chapter 8 -- New Paradigms for Engineering Plant Cell Wall Degrading Enzymes; Introduction; Engineering of Single Enzymes; Cellulosome Engineering; Multifunctional Enzyme Design; Cell Wall-Anchored Paradigms; Reflections and Perspectives
Includes bibliographical references and index.
Vendor-supplied metadata.
Elsevier
Keywords: Biomass conversion; Biomass energy; Microbial biotechnology; TECHNOLOGY & ENGINEERING / Chemical & Biochemical; Biofuels; Biomass; Renewable energy sources; Biomass conversion; Biomass energy; Microbial biotechnology; Electronic books